Global burden of occupational ergonomic factor-induced low back pain, 1990~2021: data analysis and projections of the global burden of disease - Wu, Meng; Wu, Peihong; Lu, Huaye; Han, Lei; Liu, Xin (Frontiers in Public Health, 2025)
BackgroundLow back pain (LBP) is a global epidemic that severely affects the quality of life and imposes a substantial economic burden worldwide. Occupational ergonomic factors are the most important modifiable contributors to LBP. In this study, we estimated the global burden of occupational ergonomic factor-induced LBP from 1990 to 2021 using the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2021 database and projected future trends.MethodsGlobal years lived with disability (YLDs) and age-standardized YLD rate (ASYLDR) for occupational ergonomic factor-induced LBP by sex and Socio-demographic index (SDI) among individuals aged 15–64 from 1990 to 2021 were obtained from the GBD 2021. Long-term trends were evaluated by calculating the average annual percent change (AAPC) of ASYLDR using a Joinpoint model. A Nordpred model was applied to analyze temporal changes in overall and age-specific YLDs and ASYLDR between 1990 and 2021, and to project trends from 2022 to 2045.ResultsFrom 1990 to 2021, global YLDs of occupational ergonomic factor-induced LBP increased by 40.63%. Projections indicated that all-age YLDs will exceed 15 million person-years by 2037. The ASYLDR of occupational ergonomic factor-induced LBP had shown a sustained decline since 1990, decreasing by 18.75% between 1990 and 2021, with an AAPC of −0.670% (95% confidence interval: −0.718 to −0.622). This downward trend is expected to persist until 2045. The SDI showed a negative correlation with ASYLDR (R = −0.36, p < 0.001). YLDs and ASYLDR were consistently higher in females than in males.ConclusionWhile the disease burden of occupational ergonomic factor-induced LBP has decreased, the reduction remains modest. Females, low SDI regions, and middle-aged/older adults (40–64 years) are the main contributors to the disease burden. Occupational ergonomic factor-induced LBP remains a critical public health problem that requires urgent attention to find global, comprehensive, effective, and targeted prevention strategies.